Control theory - Leigh, J. R. (Institution of Electrical Engineers, 2004)
This fully revised and updated edition of ""Control Theory"" addresses recent developments in the field. It discusses how the rise of H8 and similar approaches has allowed a combination of practicality, rigor and user interaction to be brought to bear on complex control problems and has helped bridge the gap between control theory and practice. The book also examines the effects of the rise of artificial intelligence techniques and the increasing availability of comprehensive software packages. The book concentrates on the structure, principles and context of control theory, and will be of int.
Keywords: Automatic control.; Control theory.; elektronické knihy; electronic books